If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (2x + 9)(6x + -7) = 0 Reorder the terms: (9 + 2x)(6x + -7) = 0 Reorder the terms: (9 + 2x)(-7 + 6x) = 0 Multiply (9 + 2x) * (-7 + 6x) (9(-7 + 6x) + 2x * (-7 + 6x)) = 0 ((-7 * 9 + 6x * 9) + 2x * (-7 + 6x)) = 0 ((-63 + 54x) + 2x * (-7 + 6x)) = 0 (-63 + 54x + (-7 * 2x + 6x * 2x)) = 0 (-63 + 54x + (-14x + 12x2)) = 0 Combine like terms: 54x + -14x = 40x (-63 + 40x + 12x2) = 0 Solving -63 + 40x + 12x2 = 0 Solving for variable 'x'. Factor a trinomial. (-9 + -2x)(7 + -6x) = 0Subproblem 1
Set the factor '(-9 + -2x)' equal to zero and attempt to solve: Simplifying -9 + -2x = 0 Solving -9 + -2x = 0 Move all terms containing x to the left, all other terms to the right. Add '9' to each side of the equation. -9 + 9 + -2x = 0 + 9 Combine like terms: -9 + 9 = 0 0 + -2x = 0 + 9 -2x = 0 + 9 Combine like terms: 0 + 9 = 9 -2x = 9 Divide each side by '-2'. x = -4.5 Simplifying x = -4.5Subproblem 2
Set the factor '(7 + -6x)' equal to zero and attempt to solve: Simplifying 7 + -6x = 0 Solving 7 + -6x = 0 Move all terms containing x to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -7 + -6x = 0 + -7 Combine like terms: 7 + -7 = 0 0 + -6x = 0 + -7 -6x = 0 + -7 Combine like terms: 0 + -7 = -7 -6x = -7 Divide each side by '-6'. x = 1.166666667 Simplifying x = 1.166666667Solution
x = {-4.5, 1.166666667}
| (4x-7)= | | (x^2)-6(x)-1=0 | | 9w^6+42w^5+24w^4= | | 24x-36x^2=0 | | 8(6x-7)=96x | | -1/4(12x+4)+1/7(49x+21) | | 8-7x=119-28x | | 2x+3=x+85 | | -x^2+17x-23=5x+9 | | x^4-4x^2-2=0 | | 1.16y=y+1+0.5 | | 50-7x=20x+20 | | 5x+4=28x+12 | | 1.16y=y+1+0.3 | | 1.2=2x/3+5.1 | | 1.16y=y+1+1 | | x/5+8=6 | | -x^2+2x+58=-x+4 | | x/5+12=-20 | | 5x/2=11+2x/3 | | 3x^2y-6xy^2= | | 6x+13=69-3x | | 1/3(5-3x)=5/6(x-2) | | x-39=79 | | 6(3x-12)=54x | | 13x+12=5x+10 | | 5m+20=6m+12 | | -3(x-2.7)=1.8 | | 5y^2-17y+14= | | -5x^2-5x+10=-2x^2-4x+7 | | 7(x-3)=-4x+89 | | 8.4=-6(a+2.4) |